Unsports[Man]like Outdoor Public Spaces: Exercising Women's Learning to Navigate Violence and Safety During Hours of Heightened Risk - Mattyna L Stephens (Adult Education Research Conference, 2024)
This study aimed to explore the perspectives of women who exercise in outdoor public spaces during hours of heightened risk and to offer insights to other women and organizations.
Keywords: exercising women; violence; organizational justice; feminist theory; informal learning